IMPLEMENTASI MODEL PEMBELAJARAN ROLE PLAYING DALAM MENINGKATKAN KEMAMPUAN MENULIS TEKS PROSEDUR PADA SISWA KELAS VII SEKOLAH MENENGAH PERTAMA (SMP) - Via Nugraha; Ratih Sapdiani (Jurnal Akrab Juara, 2019)
The objectives of the study were: 1) to explain the implementation of role playing learning models in learning materials for writing text procedures, and 2) to explain the calculation of the value of pre-test and post-test in the experimental class and control of experimental and control pre-test. This research shows that the implementation of the role playing learning model is carried out in accordance with the Learning Implementation Plan (RPP). The hypothesis of this study is to increase the results of post-test results compared to pre-test in the experimental class, and the acquisition of post-test scores in the experimental group is higher than the control group. The results of statistical calculations show a significance of <0.05, which means that Ho is rejected and Ha is accepted. Both classes experienced an increase in post-test acquisition. However, the experimental class shows more significant results than the control class. The results of the average in the experimental class were 62.16 during pre-test and 75.32 during post-test. Meanwhile, the control class during pre-test was 63.04 and 70.24 at the post-test period. These results indicate that the role playing model is more suitable for use in learning to write procedure texts.